SEJARAH ”LUBANG JAPANG” SEBAGAI TEMPAT PERLINDUNGAN DARI SEKUTU DI BUKITTINGGI TAHUN 1942-1945 - Fetra Yurita Fetra Yurita; Bedriati Ibrahim Bedriati Ibrahim; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Japanese hole or Lubang Japang (Minang language designation) is one of the attractions that exist in the area of West Sumatra exactly in the middle of the park in Sianok canyon panorama below the town of Bukittinggi. Japang hole has a length of 1400 m and winding. The tunnel is located approximately two meters below the ground surface Bukittinggi. Japang tunnel or hole is a long historic tunnel for Indonesia in general because Japang hole is a foxhole or Japanese soldiers hiding place in the face of war. Japang holes built with the purpose of defense interests of the Japanese army in World War II and the Greater East Asia War. The purpose of this study was (1) To find out when the Japanese hole was made, (2) To know how chronological manufacture Japanese hole in Bukittinggi, (3) To find out who is involved in the manufacture of Japanese hole in Bukittinggi (4) For megetahui how the role of the people Indonesia in the manufacture of Japanese hole, (5) To know how to influence Japanese hole to Bukittinggi. This research method is the historical method or methods of history. The place is the town of Bukittinggi research that one historical object Japanese hole. When the study for 4 months, starting from the research proposal seminar continued with a thesis to graduate exam. Data collection techniques include five techniques namely engineering literature, technical documentation, interview techniques, observation techniques and data analysis techniques. The results of this study are Japang hole he made this Bukittinggi has two versions, the version of the Japanese officers and one version of Indonesian workers in London who is our fighters who live in Bukittinggi Agam. Japang hole is in the road near the canyon Sianok Panorama is a strategic place for the Japanese. Underground tunnel (Lubang Japang in Panorama) This is the result of the excavation of the workers who were deployed hundreds of numbers. Soil excavated to a depth of 1,400 meters and former dig soil dumped into the canyon which is essentially a very deep depth. At that time the excavation carried out on the orders of Lt. Moritake Tanabe order for the protection of war.Keywords: History, Lubang Japang